Earnings management by health insurance companies in Brazil - Antonio Lopo Martinez; Flávio Alves de Carvalho (European Journal of Management and Business Economics (EJM&BE), 2022)
Purpose - This study examines whether Brazilian health insurance companies (HICs) engage in earnings management through discretionary accruals or operational decisions by refraining from reporting a low indicator of sustainability in the market (IDSM). Design/methodology/approach The study used the Jones and Modified Jones models to identify earnings management through discretionary accruals and used the model described by Roychowdhury to estimate the abnormal behaviors of operational decisions. Data covering 2012 to 2018 were collected from the ANS website. Findings The results show that HICs engaged in earnings management to avoid reporting a low IDSM. The findings should help health insurance clients make decisions regarding the purchase or change of health insurance. The findings should also encourage regulators to improve their evaluation of the economic and financial risks around HICs. Originality/value The National Agency of Supplementary Health (ANS) established a qualification program for HICs, monitoring them based on a set of indicators. Managers may have an incentive to use earnings management to obtain indices that meet the requirements of the ANS qualification program in order to avoid showing signs of abnormality.
Keywords: 650; Abnormal behavior; Abnormality; Earnings management; Health insurance company; Operational decision